Kerjasama Guru Bimbingan dan Konseling dengan Orangtua dalam Pengentasan Masalah Siswa Menonton Video Porno - Hotnarida Witasari (Jurnal Konseling dan Pendidikan, 2013)
The research shows that, Padangsidimpuan Public Senior High School 3 students’ behavior of watching porn video occured during teaching and learning process, during break time and when they getting bored with the routine activities. The media they use to watch porn video is handphone and Laptop. The problems found  are parents prefer hide the problem, the lackness of facility given by the headmaster, and the lackness of parents’ understanding on the importance of this cooperation.